Manajemen Talenta dalam Mewujudkan Pemimpin Berkinerja Tinggi (Studi pada Instansi Pemerintah Provinsi Bali) - Ida Ayu Rai Sri Dewi (Lembaga Administrasi Negara, 2020)
Talent management is one of the criteria for a merit system in the management of the State Civil Apparatus (ASN). Based on Law No. 5 of 2014 talent management needs to be implemented immediately, for that in research using analytical descriptive methods, the authors obtain an overview of talent management in realizing high-performance leaders, through studies at the Provincial Government of Bali. The results of interviews with resource persons, talent management is carried out in planning, recruitment, competency development, career development, promotion, succession planning to filling the position of Primary High Leaders to realize high-performance leaders, who are agile and characterized by socio-cultural values. The application of the merit system has been positively appreciated by the State Civil Apparatus Commission. Factors that influence the success of talent management include leadership commitment, job competency standards, employee competency mapping, career planning, and succession planning. Opportunities to participate in competency development, effective performance evaluation and employee talent information systems are the expectations of civil servants.Key words: Talent management, high-performance leaders, competency development, and succession planning